Agricultural Aid to Smallholder Farmers and Food Security in Cameroon - Tambe, Mbu Daniel; Ibrahim, Manu; Ngetleh, Ngesang Ngiqueh (Economic Journal of Nepal, 2015)
This study is aimed at analyzing the effects of agricultural aid to smallholder farmers on food security in Cameroon, the case of Santa Subdivision. Data was collected using questionnaires administered to 202 smallholder farmers from simple random sampling and purposive sampling techniques. Analysis was done using descriptive statistics, logistic model and covariance matrix. The results on the socioeconomic characteristics of smallholder farmers revealed that the majority of smallholder farmers’ aid beneficiaries were mostly educated married men. Results from the logistic regression showed that, agricultural aid is strongly correlating with food security, while the covariance matrix revealed that the major constraints faced by smallholder farmers are: access to farms, farm to market infrastructure, storage facilities, access to credit and application of agricultural inputs. Policy aiming at improving farmers’ access to agricultural inputs, infrastructure, capacity building, participatory management and access to credits will accelerate agricultural production in Cameroon.